Case Report and Review of Literature: Autosomal Recessive Hypophosphatemic Rickets Type 2 Caused by a Pathogenic Variant in ENPP1 Gene - Choe, Yunsoo; Shin, Choong Ho; Lee, Young Ah; Kim, Man Jin; Lee, Yun Jeong (Frontiers in Endocrinology, 2022)
Autosomal recessive hypophosphatemic rickets type 2 (ARHR2) is a rare form of hereditary rickets, which is characterized by defective bone mineralization and renal phosphate wasting due to a loss-of-function variant in the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) gene. Although pathogenic variant of ENPP1 has been known to manifest other phenotypes including arterial calcification, hearing loss, ossification of posterior longitudinal ligament, or pseudoxanthoma elasticum, there have been few reports including systematic examination in individuals diagnosed with ARHR2 to date. Herein, we report a case of ARHR2 with a bi-allelic pathogenic variant of ENPP1, in which the patient presented with gait abnormalities with severe genu varum at 26 months of age. Targeted gene panel sequencing was performed to investigate the genetic cause of rickets, and a homozygous nonsense variant in ENPP1, c.783C>G (p.Tyr261*), was identified. The patient was treated with oral phosphate and active vitamin D supplements and underwent corrective osteotomy for varus deformity. His phenotype was limited to rickets. A periodic systematic evaluation is needed to identify any comorbidities in ARHR2 patients since ENPP1 variants may present phenotypes other than rickets and symptoms may evolve or change over time.